Efektivitas Pelaksanaan Program Bimbingan dan Konseling (Studi Evaluasi Proses dan Evaluasi Produk di SMP Negeri 2 Salatiga) - Wahidin, Wahidin (JURKAM: Jurnal Konseling Andi Matappa, 2018)
Process evaluation and product evaluation are like two sides of the coin in the program of guidance and counseling services, both of which will have an impact on the performance of guidance and counseling teachers. This study aims to capture the effectiveness of the implementation of guidance and counseling programs in schools, especially through process evaluation and product evaluation. The research method used is a quantitative method, with data collection techniques in the form of questionnaires, while the analysis using descriptive statistics. The results show that product evaluation will be related to the implementation of guidance and counseling programs.